(untitled) (International journal of artificial intelligence, 2025)
This article explores the theoretical and practical aspects of applying modern, innovative, and digitally-based non-traditional teaching methods in the methodological training of future primary school teachers. The study introduces new methodological approaches such as “digital reflection”, “virtual collaboration”, “AI-assisted teaching”, “gamified methodological training”, and “micro-teaching simulator”, which correspond to the educational trends of 2025. These approaches aim to enhance future teachers’ competencies in independent thinking, rapid problem-solving, effective use of digital tools, and creative methodological decision-making. Moreover, the paper proposes a new model for analyzing and improving methodological training through artificial intelligence support.